Midlife Predictors of Health-Related Quality of Life in Older Women. (27th March 2018) - Avis, Nancy E; Colvin, Alicia; Bromberger, Joyce T; Hess, Rachel
Abstract: Background: Midlife represents an important time to evaluate health status and health behaviors that may affect health-related quality of life (HRQL) in later years. This study examines change in women's HRQL over 11 years from ages 47–59 to 57–69 and identifies midlife characteristics that predict HRQL at older ages. Methods: Physical (PCS) and mental component summaries (MCS) of the SF-36 were used to assess HRQL from 2002 to 2013 in 2, 614 women from the Study of Women's Health Across the Nation (SWAN), a multiethnic/racial cohort study. We used locally weighted scatterplot smoothing (LOESS) models to obtain unadjusted predicted mean trajectories of PCS and MCS as a function of age. Results: LOESS predicted PCS declined from 51.6 to 47.1, whereas MCS increased from 49.2 to 53.1. In multivariable models, controlling for baseline PCS, higher baseline physical activity ( p = .002) and increase in physical activity from baseline ( p < .0001) predicted better PCS. Time since baseline (ie, aging; p < .001), higher baseline body mass index ( p < .0001), increased body mass index over time ( p < .0001), smoking ( p < .05), two or more medical conditions ( p < .0001), sleep problems ( p < .0001), and urinary incontinence ( p < .0001) were related to lower PCS. Early ( p = .004) and late postmenopause ( p = .001; vs. premenopause) and aging ( p = .05) predicted higher MCS. Predictors of lower MCS were less than very good health ( p < .0001), sleep problems ( p < .0001), stressful life events ( p < .0001), higher perceived stress ( p < .0001), and higher trait anxiety ( p = .004). Race/ethnicity was related to MCS, but not PCS. Conclusions: Several potentially modifiable midlife factors, such as improved sleep hygiene, physical activity, and body mass index, might improve HRQL for older women.